OIL AND GAS POTENTIAL AND STUDY OF RESERVOIR PROPERTIES OF THE CRETACEOUS DEPOSITS OF THE YEVLAKH-AGDJABEDI DEPRESSION - Mukhtarova, Kh.; Nasibova, G.; Ismayilova, М. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The aim of the study is to substantiate the prospects for the oil and gas content of the Upper Cretaceous effusive and carbonate deposits by studying their reservoir parameters. Previous studies have established that a sedimentary complex, present in the geological structure of the Muradkhanly field, is lithologically represented by clays, siltstones, sands and sandstones, dolomites, limestones, tuffs, Upper Cretaceous porphyrites. Since this lithofacies composition of the section is of great importance as a reservoir rock, volcanic sandy tuffs, mudstones and dense sandstones of the Upper Cretaceous age have been comprehensively investigated throughout the territory. We studied carbonates of this age and found that they have compaction of varying extent and are divided into 3 groups: weakly, moderately and strongly compacted and this, in turn, has considerable effect upon the rock porosity. At the beginning of the study, the reservoir features of Meso-Cenozoic sediments in the Yevlakh-Agdjabedi depression [YAD] were studied mainly on the basis of terrigenous rocks that refer to the Cenozoic. In our studies, Cretaceous deposits were studied, which are represented by effusive, carbonate rocks with secondary reservoir properties. The reservoir properties of chalk deposits in the YAD areas were investigated on the basis of studies of core samples in laboratories. It was found that the reservoir rocks of the area under investigation are volcanic, volcanic-sedimentary and carbonate, that is, they mainly consist of fractured limestones, marls and dolomites. Studies have shown that the oil and gas content of the depression is associated mainly with carbonate and effusive reservoirs. To assess the prospects for the oil-bearing capacity of the YAD, geological sections were studied in terms of the reservoir properties of a number of structures, and on the basis of the obtained core samples data. Trend maps were compiled using the "Surfer" software. Analysis of the maps allows identifying the corresponding zones of carbonate content, permeability, porosity, characterized by high, medium and low values. According to the carbonate readings, the studied territory does not have a strict distribution pattern and, according to the permeability distribution data, it is divided into two zones: the northern zone with average and the southern one with low values. There is, to a certain extent, pattern for variation of the values of carbonate content and permeability, and this can be explained by the secondary transformation of the reservoir properties of carbonate rocks, as a result of which permeability and porosity changed. Porosity distribution, to some extent, is aligned with permeability. Inverse relationship between the values of porosity and permeability can be explained with the filling of voids with cement material in the rock formation environment. Currently, in order to continue exploration and drilling works, comprehensive geological and geophysical studies are being carried out, as a result of which comparison of data obtained will make it possible to assess the prospects of each structure in more detail.
Keywords: thickness; core; Mesozoic; carbonate content; porosity; permeability; prospects